“Embarrassing and disgraceful”: technology-facilitated sexual violence and victim’s healing process - Gita Anita; Deddy Mulyana; Nindi Aristi (Jurnal Kajian Komunikasi, 2022)
This study aims to reveal the communication experience of victims of online gender-based violence and the healing process from the trauma they experienced. The main research questions are how victims experience violence online, what motives encourage perpetrators to commit violence from the victim’s perspective, the meaning of the communication experience, and the victim’s process of healing the traumatic experience. In this qualitative study, phenomenological methods and symbolic interaction theory were employed. The research subjects are women victims of online gender-based violence cases. Informants were selected through a purposive sampling technique. The results showed that most cases of threats of spreading intimate photos or videos were experienced by victims when they asked for a breakup or did not follow the wishes of the perpetrator. Victims of violence in the online realm are also vulnerable to multiple layers of violence. The video is used as a tool for the perpetrator so that the victim does not refuse to have sex with the perpetrator. The impact experienced by the victim is psychological loss, social isolation, and limited mobility. The three motives behind the above cases are relational, sextortion or extortion, and unknown motives. The meanings obtained from the communication experience of victims are shame, disgrace, loss of identity, feeling tarnished, and having mistrust of the opposite sex. The victims used various ways to heal themselves from the trauma, namely getting closer to God, telling stories to friends, and consulting psychologists.